Ultrasound Assessment of Fetal Biometry at Raden Mattaher Hospital - herlambang, Herlambang; Firmansyah, Frimansyah; Kesty, Cindy; Aryani, Puspa Muthia; Divanna, Diora Asha (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Fetal biometry is the cornerstone of modern prenatal care. This study aims to assess fetal size (fetal biometry at a given time point compared to normal charts) and estimate fetal weight (EFW) using the Hadlock formula. Methods: A descriptive retrospective study in order to establish fetal biometry in the third trimester of pregnancy and incorporated into Hadlock's formula to estimate fetal weight. Four fetal biometry measurements (BPD, HC, AC and FL) were collected from ultrasonography examination results in Raden Mattaher General Hospital. Data were documented using case report form and being tabulated using Microsoft Excel 2011 Version 14.7.0 (161029). All data were analyzed using SPSS 25.0. Results: There were 100 data of pregnant women who underwent fetal biometry ultrasound examinations from February 2021 to April 2023, 100 data samples were obtained that met the criteria for inclusion in the study. The data was distributed based on gestational age from 9 weeks to 41 weeks of gestation. Data on four biometric parameters were collected and calculated using Hadlock formula to obtain an estimate of fetal weight. In the study, it was estimated the weight of the fetus at the 33rd week of pregnancy was 1800 grams, which was in the 10-50 percentile on Hadlock curve. Conclusion: Assessment of fetal biometry is one of the main components of modern prenatal care. Accurate pregnancy dating is essential for further interpretation of both fetal size and growth. Measuring biometrics parameters, including Head Circumference (HC), Biparietal Diameter (BPD), Abdominal Circumference (AC), and Femur Length (FL), and combining them into an estimated fetal weight should be part of the routine ultrasound exam.